Uso del flushing en la iatf y su efecto en la fertilidad del ganado mestizo brahman. - Silva Plaza, Patricia Paulette; Villacis Revilla, Domenika Rosario (Machala : Universidad Técnica de Machala, 2023)
The livestock sector in Ecuador is led by more than 4.6 million bovine and buffalo animals, making it one of the fundamental pillars of agricultural production in the country. Breeding involves various breeds such as Brown Swiss, Brahman, Holstein, and Creole. However, low pregnancy rates are observed due to factors such as poor quality pastures or feeding, improper animal management, and deficient sanitary conditions, all of which affect reproduction and production. This research aims to implement an energy flushing technique to increase the pregnancy rate in conjunction with the Timed Artificial Insemination (IATF) technique. Flushing, a technique involving modifying the livestock's diet to alter hormone concentrations, plays a crucial role in the reproductive and fertility parameters of the animals. Hormones involved in follicular development and ovarian morphology are affected by this practice, directly impacting oocytes and embryos in both heifers and cows. Timed Artificial Insemination (IATF) is a technique that synchronizes estrus in multiple cows simultaneously using hormones, facilitating artificial insemination within a specific period. This practice reduces postpartum open days, improves genetics, and facilitates calving, albeit requiring a higher initial investment. To effectively carry out IATF, factors such as cows' body condition, proper health plan, high-quality semen, good infrastructure, and experience in artificial insemination must be considered. This study can have a significant impact on both large and small livestock farms through the administration of flushing, allowing for an increase in the pregnancy rate, as demonstrated in our work, which raised it by 30%. This dietary supplement aids in livestock fertility in conjunction with the IATF technique. Several factors influencing pregnancy, such as body condition, animal behavior, and feeding, are taken into account.
El sector ganadero en Ecuador está liderado por más de 4.6 millones de animales bovinos y bufalinos, siendo uno de los pilares fundamentales de la producción agropecuaria en el país. La cría involucra diversas razas como Brown Swiss, Brahman, Holstein y Criolla. Sin embargo, los índices de preñez son bajos debido a factores como la mala calidad de pastos o alimentación, mal manejo de los animales y deficientes condiciones sanitarias, lo que afecta la reproducción y producción. Por este motivo esta investigación busca implementar un flushing energético para incrementar el índice de preñez en conjunto con la técnica Inseminación Artificial a Tiempo Fijo (IATF). El flushing, una técnica que implica modificar la dieta del ganado para alterar las concentraciones hormonales, juega un papel crucial en los parámetros reproductivos y fértiles de los animales. Las hormonas involucradas en el desarrollo folicular y la morfología ovárica se ven afectadas por esta práctica, impactando directamente en ovocitos y embriones tanto en novillas como vacas. La Inseminación Artificial a Tiempo Fijo (IATF) es una técnica que sincroniza el celo en varias vacas simultáneamente mediante hormonas, facilitando la inseminación artificial en un período específico. Esta práctica reduce los días abiertos postparto, mejora la genética y facilita los partos, aunque implica una inversión inicial mayor. Para llevar a cabo la IATF efectivamente, se deben considerar factores como la condición corporal de las vacas, un plan sanitario adecuado, semen de alta calidad, buena infraestructura y experiencia en inseminación artificial.
Keywords: IATF; HORMONAS; SINCRONIZACION; FLUSHING